1993
DOI: 10.1128/aac.37.5.1160
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the anti-human immunodeficiency virus nucleoside analog stavudine in cynomolgus monkeys

Abstract: Stavudine was administered (15 mg/kg of body weight) intravenously and orally to two monkeys in a randomized crossover study. Plasma and urine samples were analyzed for stavudine by high-performance liquid chromatography, and pharmacokinetic parameters were derived by a noncompartmental method. Total body clearance of stavudine was 0.64 liters/h/kg, with a steady-state volume of distribution of 0.68 liters/kg, a terminal half-life of 0.83 h, a urinary recovery of 44%, and an oral bioavailability of 80%. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
4
4
0
Order By: Relevance
“…The pharmacokinetic parameters of stavudine and di-danosine are in general agreement with those previously reported for monkeys (3,7,18,19,21,22) and humans (5,6,8).…”
supporting
confidence: 91%
“…The pharmacokinetic parameters of stavudine and di-danosine are in general agreement with those previously reported for monkeys (3,7,18,19,21,22) and humans (5,6,8).…”
supporting
confidence: 91%
“…The route of elimination in humans is in concurrence with the findings in mice, rats, and monkeys (Russell et al, 1990;Cretton et al, 1993;Kaul and Dandekar, 1993;Kaul et al, 1999). The extent of absorption and oral bioavailability of stavudine in humans was at least 95 and 67%, respectively, based on urinary recovery values of TRA and stavudine.…”
Section: Disposition Of Stavudine In Humanssupporting
confidence: 66%
“…14 C]stavudine, [4- 14 C]stavudine, or [5-3 H]stavudine (all labels on the thymidine moiety) showed that the compound was well absorbed (Russell et al, 1990;Cretton et al, 1993;Kaul and Dandekar, 1993;Kaul et al, 1999). The recovery of the drug in excreta varied in animals, with the majority of the dose recovered in the urine.…”
mentioning
confidence: 99%
“…The oral dose of 60 mg/kg was used for AZT and D4T with rhesus monkeys (7,39). Oral bioavailabilities of D4T were 25 to 51% in rhesus monkeys (39), 77 to 83% in cynomolgus monkeys (25), and almost 100% in humans and mice (36,38). High C max values were observed with APD, the DXG prodrug, after oral administration (C max of DXG ϭ 50 to 60 M within 0.25 to 0.5 h) (11) ; k 21 ϭ 0.51 h Ϫ1 ) are suggestive of rapid equilibration of the drug between the central and peripheral compartments.…”
Section: Discussionmentioning
confidence: 99%